(untitled) (Research, Society and Development, 2022)
Pharmacoderma is an adverse dermatological reaction to a drug, wich is, any side effect related to the skin and/or its adnexa, such as mucous membranes, hair and nails, in its structure or function. Medicines containing drugs that can cause pharmacoderma are unknown to the population. Pharmacoderma are among the most common adverse drug reactions, assuming multiple clinical aspects, from solitary lesions to generalized conditions. In this sense, bringing useful information to readers about the occurrence of pharmacoderma cases in recent years and making a survey of the main responsible pharmacological classes is of paramount importance because pharmacoderma is increasingly frequent, causing great discomfort and pain to patients. The work was carried out through a systematic review of the literature on pharmacoderma. The search was carried out using the keywords pharmacodermia, in the Google Academic and Regional Portal of the VHL (Virtual Health Library) using the Scientific Electronic Library Online (SCIELO) databases, Latin American and Caribbean Literature in Science of Health (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE), among others, resulting in 153 scientific papers. We found that the pharmacological classes with the highest incidence in cases of pharmacoderma were anti-inflammatory, chemotherapeutic, anticonvulsant, anxiolytic, antihypertensive and antibiotic, however all medication can cause adverse effects such as pharmacoderma. These classes are among the most prescribed in the world, therefore, the contact of the multidisciplinary team and the clinical pharmacy are essential for the rapid identification of possible pharmacoderma.